Impact of Plant Weeds on Grass Availability in Gaur (Bos gaurus H. Smith, 1827) Foraging Areas of Mudumalai Tiger Reserve, Southern India - Kumar, M. Ashok; Nagarajan, R.; Ilayaraja, R.; Swaminathan, S.; Desai, Ajay A. (Indian Forester, 2012)
Invasive species are regarded as one of the largest threats to biodiversity but little is known about the invasion of exotic plants into the tropical forest. The per cent grass availability in gaur (Bos gaurus H. Smith, 1827) foraging areas in three different habitats namely dry deciduous forest, moist deciduous forest and thorn forest in relation to weed category areas viz., Lantana camara invasion areas, Chromolaena odorata invasion areas, 'both weeds invasion' and 'weed-free' areas were investigated in Mudumalai Tiger Reserve between November 2003 and April 2004. The overall mean per cent grass availability was 28.52±26.81/m2 (n=7343). The overall mean density of L. camara and C. odorata were 2.2±5.75/50m2 (n=8090) and 10.7±14.6/50m2 (n=8090) respectively. Among the habitats, the dry deciduous forest had maximum availability of grass (%) followed by thorn forest and moist deciduous forest. The per cent availability of grass was highest in the weed free areas of dry deciduous forest (54.0227.28%) and lowest in L. camara areas of thorn forest (14.52±14.45%). In all the habitats there was a significant variation among the weed category areas with reference to the per cent availability of grass. The densities of L. camara and C. odorata negatively influenced the per cent grass availability. The Standardized Partial Regression Coefficients of multiple regression equation model indicated that the C. odorata had the primary influence on the grass growth followed by L. camara.